2019
DOI: 10.1038/s41436-019-0557-3
|View full text |Cite|
|
Sign up to set email alerts
|

Variants in MED12L, encoding a subunit of the mediator kinase module, are responsible for intellectual disability associated with transcriptional defect

Abstract: Purpose-Mediator is a multiprotein complex that allows the transfer of genetic information from DNA binding proteins to the RNA polymerase II during transcription initiation. MED12L is a subunit of the kinase module, which is one of the four sub-complexes of the mediator complex. Other subunits of the kinase module have been already implicated in intellectual disability, namely MED12, MED13L, MED13 and CDK19. Methods-We describe an international cohort of seven affected individuals harboring variants involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…Therefore, another interpretation of the knockout results is that removing Med13 or Med13L may invoke a gene dosage-related phenotype. For example, recent studies found that MED13 or MED13L haploinsufficiency results in several overlapping, but not identical, developmental syndromes (41)(42)(43)(44)(45)(46). Therefore, transcriptional control by Med13 and Med13L may be exquisitely sensitive to gene copy number.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, another interpretation of the knockout results is that removing Med13 or Med13L may invoke a gene dosage-related phenotype. For example, recent studies found that MED13 or MED13L haploinsufficiency results in several overlapping, but not identical, developmental syndromes (41)(42)(43)(44)(45)(46). Therefore, transcriptional control by Med13 and Med13L may be exquisitely sensitive to gene copy number.…”
Section: Discussionmentioning
confidence: 99%
“…To find candidate genes that participate in osteoclastogenesis after treatment with myostatin, a CHIP assay was performed, and 20 genes that were clearly upregulated or downregulated were selected. These differentially expressed genes play important roles in inflammation ( Slominski et al, 2020 ), calcium channels ( Fenninger et al, 2019 ), transcription ( Nizon et al, 2019 ; Gura et al, 2020 ), cell differentiation ( Gobbi et al, 2019 ), and cell apoptosis ( Morris et al, 2020 ). II9, for example, is critical for mast cell-driven diseases ( Abdul Qayum et al, 2019 ), while Htatip2 can regulate the cell cycle and promote cell apoptosis ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, another interpretation of the knockout results is that removing Med13 or Med13L may invoke a gene dosage-related phenotype. For example, recent studies found that MED13 or MED13L haploinsufficiency results in several overlapping, but not identical, developmental syndromes (40)(41)(42)(43)(44)(45). Therefore, transcriptional control by Med13 and Med13L may be exquisitely sensitive to gene copy number.…”
Section: Discussionmentioning
confidence: 99%